2015
DOI: 10.1016/j.sbspro.2015.11.579
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Learning Approach to Delivering Professional Modules to Bachelor and Master Students: TPU Experience

Abstract: Modern tendencies in engineering education set certain requirements on the competences to be obtained. To enable a future engineer to work at a highly competitive level and become an internationally recognized specialist, they must possess advanced English speaking and writing skills. At present most universities introduce educational programs that attract bright domestic and international students to ensure that they are in demand at the global market. The Strategic Program on Competitiveness Enhancement of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…are all subjects of vivid scholarly discussions and critical scientific investigation [19,20]. Growing interest towards project work among university students of various academic fields and levels can be acknowledged [see [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The authors have analysed more than 50 research publications and summarized the main directions of the international academic research on projectbased learning in higher education.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…are all subjects of vivid scholarly discussions and critical scientific investigation [19,20]. Growing interest towards project work among university students of various academic fields and levels can be acknowledged [see [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The authors have analysed more than 50 research publications and summarized the main directions of the international academic research on projectbased learning in higher education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To reach the aim of the present study, a whole number of specific points addressed in international academic publications have been investigated. Among them there are problems of project management, types of projects, approaches to project work, stages of project implementation, evaluation of cooperative project work, students' competence development within project-based learning, knowledge transfer in project-based learning and other features of project method use in the educational space [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The hermeneutical analysis of academic literature on the topic, critical reflection on shared professional experience of the authors as well as their professional discussions on the related issues of projectbased learning have resulted in:…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was found that second-, third-and fourth-year students have a tendency towards a professional activity in the form of intellectual work (tendency towards an intellectual activity). However, it was found that while most second-year students base their labour-related behaviour on motives of self-affirmation, third-and fourth-year students are guided by motives of professional excellence (Red'ko et al, 2015;Reka et al, 2015;Saltymakov & Frantcuzskaia, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to [2], "The cooperative learning approach is easily combined with many other approaches to teaching and learning". Slavin's cooperative learning study suggests that cooperative learning enhances interaction among students by providing them with fun activities together and establishing their basis for sharing commonalities (group membership), as well as engaging them to work together to achieve goals together [3,4].…”
Section: Introductionmentioning
confidence: 99%